Magnitude and determinants of glaucoma in type II diabetics: A hospital based cross-sectional study in Maharashtra, India - Dharmadhikari, Sheetal (Oman J Ophthalmol, 2015)
BACKGROUND: Glaucoma and diabetes have a common pathogenesis. We estimated the magnitude and determinants of glaucoma in adults with type II diabetes who presented to a tertiary level eye center in 2010. STUDY TYPE: A cross-sectional survey. METHODS: Diabetes was diagnosed by history and measurement of blood sugar levels. Glaucoma was diagnosed by assessing optic disc morphology, visual fields, and intraocular pressure. Data were collected on patient demographics, clinical characteristics of diabetes and ocular status through interviews and measurements. The prevalence of glaucoma in diabetics was estimated, and variables were analyzed for an association to glaucoma. The 95% confidence intervals (CIs) were calculated. Statistical significance was indicated by P < 0.05. RESULTS: The study cohort was comprised of 841 diabetics. The mean age of the cohort was 53.8 ± 10.7 years. There were 320 (38%) females. The prevalence of glaucoma was 15.6% (95% CI: 13.1-18.1). More than 75% of the diabetics had no evidence of diabetic retinopathy (DR). Half of the diabetics with glaucoma had primary open angle glaucoma. The presence of glaucoma was significantly associated to the duration of diabetes (Chi-square = 10.1, degree of freedom = 3, P = 0.001). The presence of DR was not significantly associated to the presence of glaucoma (odds ratio [OR] = 1.4 [95% CI: 0.88-1.2]). The duration of diabetes (adjusted OR = 1.03) was an independent predictor of glaucoma in at least one eye. CONCLUSIONS: More than one-sixth of diabetics in this study had glaucoma. Opportunistic screening for glaucoma during DR screening results in an acceptable yield of glaucoma cases.